The Charter and Code of the Ordinances of Yazoo City 174, § 298 (1908) - (:unkn) unknown (My University, 1906)
Ch. 20, § 298 : Any father who shall knowingly suffer or permit any son under the age of sixteen years to have or to own, or to carry concealed, in whole or in part, any weapon the carrying of which concealed is prohibited, shall be guilty of a misdemeanor, and, on conviction, shall be fined not less than twenty dollars nor more than two hundred dollars, or may be imprisoned not more than sixty days in the county jail, or both.
Keywords: POSSESSION - MINORS